Coupling Internal Erosion through Concrete Face Rockfill Dams with Damage in Face Slab under Impounding. Issue 5 (March 2019) - Shakya, Chandan; Luo, Xianqi; Bi, Jinfeng; Zhang, Haitao; He, Gaofeng
Abstract: This study describes a way to realistically model the internal erosion after of damage in the concrete face of a concrete face rockfill dam (CFRD). The study uses a 2D plane strain model of Tianshengqiao dam's geometry as an example, with and without consideration to erosion of the underlying cushion and transition layers. In order to accomplish this, Mazars' concrete damage model, which is a continuum damage model, was coupled with permeability relationships on the face slab; and poroelastic model was used in conjunction with Sterpi's erosion model for the underlying cushion and transition layers. Two scenarios were studied: without considering erosion and considering erosion. Results reveal that when the reservoir is linearly impounded damage in the face slab is concentrated to the lower quarter of the slab, and internal erosion will occur at the toe of the dam. After more fine particles are lost, the mechanical and hydraulic properties of the dam will change and the dam safety can be compromised.